Study on the Impact of Smart and Innovative Delocalization Practices on International Trade - et. al., Ibrahim Assabane, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Faced with cumulative competition linked to the globalization of markets, and increasingly strong demands in terms of performance, many firms are led to ask the question of relocating either part or all of their activities. Relocation is a strategic decision which obliges companies to review and reconfigure their operations management methods, in particular those concerning the supply chain. The working objective is to identify the key factors to take into consideration for the design of the supply chain in the context of delocalization. First, we tackle the problem of defining delocalization and the supply chain. Next, we review the literature to define the specifics of the problem of relocation and their impact on international trade, notably the case of Morocco, and thus identify all the factors and constraints to be taken into account when reconfiguring the global supply chain in order to adapt it to the context of the practice of intelligent delocalization.